Does the virtue of Islam gives significant impact on social enterprise? - Zainon, Saunah; Soo, Kum Yoke; Mohamed Yunos, Rahimah; Md Yatim, Nurul Huda; Mokhtar, Rashidah; Japelus, Nur Eyliawati (Faculty of Administrative Science and Policy Studies, 2023)
The purpose of Islamic social enterprise is to carry out Islamic objectives in its activities and operations. The Islamic objective, which is known as maqasid syariah, is an essential foundation in any Islamic organization are designed to promote benefits and repel harms. Maqasid syariah calls for establishment of justice, elimination of unfairness and alleviation of private. Therefore, this study sought to see whether the instillation’s of ISE can contribute to the better social enterprises by using ISE index measurement as it involves the Shari‟ah compliant trading activities to ensure the sustainability of ISE. Without clear objectives, ISEs which emphasizes on the combination of economic and social objectives in an organization, might not be able to run their operations and activities smoothly.